Model Net Benefit Aplikasi Coretax dengan Metode Delone & Mclean - Nunuk Latifah; Rani Arifah Normawati; Sandi Eka Suprajang (BRILIANT: Jurnal Riset dan Konseptual, 2026)
To support economic transformation and enhance the quality of economic growth in the taxation sector, the Indonesian government has reformed its tax administration system through the implementation of the Coretax application. Coretax is an integrated core tax administration system designed to unify all tax administration processes within a single digital platform to improve efficiency, transparency, and the quality of tax services. However, the success of system implementation is not solely determined by technological adoption, but also by the extent to which the system delivers tangible benefits to its users. This study aims to develop a conceptual model for evaluating the success of Coretax implementation by adapting the DeLone and McLean Information Systems Success Model. The study employs a conceptual research approach through literature review and synthesis without involving empirical data collection. The proposed model consists of six main constructs: Coretax System Quality, Coretax Information Quality, Coretax Service Quality, Coretax Use, Coretax User Satisfaction, and Net Benefits of Coretax Implementation. The findings result in a conceptual framework and hypothesis model that may serve as a foundation for future empirical studies in evaluating the effectiveness of Coretax implementation in Indonesia.